2016
DOI: 10.1002/hbm.23107
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal salience signaling in schizophrenia: The role of integrative beta oscillations

Abstract: Aberrant salience attribution and cerebral dysconnectivity both have strong evidential support as core dysfunctions in schizophrenia. Aberrant salience arising from an excess of dopamine activity has been implicated in delusions and hallucinations, exaggerating the significance of everyday occurrences and thus leading to perceptual distortions and delusional causal inferences. Meanwhile, abnormalities in key nodes of a salience brain network have been implicated in other characteristic symptoms, including the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
51
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 54 publications
(77 reference statements)
9
51
0
Order By: Relevance
“…Similar to LEP responses, vertex potentials elicited by intense stimuli belonging to different sensory modalities (Mouraux & Iannetti, ) largely reflect saliency‐related neural processes possibly related to the detection of relevant changes in the sensory environment (Downar, Crawley, Mikulis, & Davis, ). Considering that N2 wave is mainly generated from the insula that is an interoceptive integration brain structure playing a crucial role in the salience network, as it conveys multisensory information about internal body state and external surrounding environment (Craig, ), previous studies suggested that dysfunction of sensory information processing across modalities in SCZ patients could represent an epiphenomenon of salience network dysfunctions (Alustiza et al, ; Liddle et al, ; Minichino et al, ; Palaniyappan & Liddle, ; Potvin et al, ; Smucny, Wylie, Kronberg, Legget, & Tregellas, ). The salience network is involved in detecting and filtering salient stimuli and functions to segregate the most prominent information among internal and external stimuli in order to guide behavior (Legrain, Iannetti, Plaghki, & Mouraux, ; Mouraux, Diukova, Lee, Wise, & Iannetti, ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to LEP responses, vertex potentials elicited by intense stimuli belonging to different sensory modalities (Mouraux & Iannetti, ) largely reflect saliency‐related neural processes possibly related to the detection of relevant changes in the sensory environment (Downar, Crawley, Mikulis, & Davis, ). Considering that N2 wave is mainly generated from the insula that is an interoceptive integration brain structure playing a crucial role in the salience network, as it conveys multisensory information about internal body state and external surrounding environment (Craig, ), previous studies suggested that dysfunction of sensory information processing across modalities in SCZ patients could represent an epiphenomenon of salience network dysfunctions (Alustiza et al, ; Liddle et al, ; Minichino et al, ; Palaniyappan & Liddle, ; Potvin et al, ; Smucny, Wylie, Kronberg, Legget, & Tregellas, ). The salience network is involved in detecting and filtering salient stimuli and functions to segregate the most prominent information among internal and external stimuli in order to guide behavior (Legrain, Iannetti, Plaghki, & Mouraux, ; Mouraux, Diukova, Lee, Wise, & Iannetti, ).…”
Section: Discussionmentioning
confidence: 99%
“…There are a number studies which report that beta‐suppression can be elicited even in the absence of direct force output. For example, beta power loss is observed in motor planning [Brookes et al, ; Liddle et al, ; Pastötter et al, ; Tzagarakis et al, ; Van Wijk et al, ] and motor imagery [Pfurtscheller et al, ; Schnitzler et al, ]. Given that beta MRBD can occur with no movement, it is perhaps unsurprising that MRBD itself does not modulate with force or RFD.…”
Section: Discussionmentioning
confidence: 99%
“…Although our findings show that PMBR is modulated by both force and RFD, it should be made clear that these are unlikely to reflect the only parameters upon which PMBR depends. Similar to MRBD, the PMBR is also observed in the absence of actual movement (for example PMBR occurs following movement planning but in the absence of an actual movement [Liddle et al, ]. It follows therefore that PMBR is a complex signal feature modulated by cognitive processes as well as sensory input and movement parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Oscillations have also been closely associated with communication in the brain (Fries, ). Beta oscillations have been linked to resting‐state networks (Brookes et al, a; Hipp et al, ; Siegel et al, ) and the PMBR in particular has been associated with long‐range connectivity in the sensorimotor system (Donner and Siegel, ; Liddle et al, ; Vidaurre et al, ). Similarly gamma oscillations have, for example, been related to feature binding in the visual system (Tallon‐Baudry and Bertrand, ).…”
Section: Introductionmentioning
confidence: 99%